A Bloc of CODED-OFDM and WiMAX overshadowing OFDM: A Survey - Behl, Garima; Rishi, H.P.S; Kaur, Dalveer (International Journal of Computer Sciences and Engineering, 2019)
The latest favorable technology which delivers to the customer end data facilities at a high speed is the Worldwide Interoperability for Microwaves Access (WiMAX). By observing the foundation of the WiMAX physical layer an understanding has been superlatively attained regarding the system of WiMAX. The foundation of the WiMAX physical layer is discussed in this paper. The studies and research of the students and scholars are based on the meadow of WiMAX can use this model as a helpful reserve. By using some kind of channel coding the performance can be augmented. Coded-OFDM (COFDM) is scheme this form of implementation is termed as. The reimbursements of using COFDM in a WiMAX system have also conversed in this paper.